PERFORMA PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN SELUANG (Rasbora einthovenii) PADA PERLAKUAN pH YANG BERBEDA - Dobi Irawan; Suci Puspita Sari; Eva Prasetiyono; Ahmad Fahrul Syarif (Jurusan Akuakultur, Universitas Bangka Belitung, 2019)
Ornamental fish have a good potential to develop in Indonesia. Seluang (Rasbora enthovenii) is an endemic fish in the waters of Bangka Belitung. The factor that affects the survival rate and growth is pH. The purpose of this research is to know the effect of pH on survival rate and growth. The research has been done in October and November 2017. The experimental design used in the study was a randomized complete design (RAL) with 4 treatments and 3 replicated. The result of pH variance affects the survival rate. Based on the Duncan test, the treatment of pH 6,0 - 6,5 has a significant effect on the survival rate. The results of the Duncan test for all treatments don't have a significant effect on growth. The conclusion of the research is pH 6,0 - 6,5 gives the optimum effect for survival rate, on 96,66 ± 0,57%. All treatments don't have a significant effect on growth (P> 0.05).